Leading a curriculum design of care through courage in knowledge and action (Journal of Applied Learning and Teaching, 2026)
This paper explores what happens when you set out to lead a caring curriculum program design in a range of international contexts over several years with the premise of a shared vision.  Through a single composite case approach, we have captured the essence of our learnings by combining our individual accounts of eleven programs across a range of contexts to form a single composite case which sought to capture the macro-, meso-, and micro- factors at play. Employing collaborative autoethnography (CAE) and a metaphorical, three-dimensional personal narrative inquiry framework, the data (as moments and reflections recounted) emerged through close analyses of the experiences of two senior education leaders. We identified in our data the three themes as described in the literature: curriculum, leadership and care. A further sub-theme revealed that we, as leaders, care for others. However, while we enacted transrelational leadership, we were thwarted in our goal at all levels of the system. The study tells the story of how, where and why we failed. Rather than experiencing failure as a source of shame and avoiding it, we grew from the lessons learned. Key to our findings is the creation of the term “curriculum of care in higher education”. This idea is new to curriculum design discourse in higher education. It is defined as advocating for an environment where we are all included, supported, belong and feel safe, brave and care for each other. There is a commitment to asking ‘what happened to you?’ What is integral is the nature of academics’ and students’ agency in their work.